Changes in the expression of splicing factor transcripts and variations in alternative splicing are associated with lifespan in mice and humans. Issue 5 (30th June 2016) - Lee, Benjamin P.; Pilling, Luke C.; Emond, Florence; Flurkey, Kevin; Harrison, David E.; Yuan, Rong; Peters, Luanne L.; Kuchel, George A.; Ferrucci, Luigi; Melzer, David; Harries, Lorna W.
Summary: Dysregulation of splicing factor expression and altered alternative splicing are associated with aging in humans and other species, and also with replicative senescence in cultured cells. Here, we assess whether expression changes of key splicing regulator genes and consequent effects on alternative splicing are also associated with strain longevity in old and young mice, across 6 different mouse strains with varying lifespan (A/J, NOD.B10Sn‐H2 b /J, PWD.Phj, 129S1/SvlmJ, C57BL/6J and WSB/EiJ). Splicing factor expression and changes to alternative splicing were associated with strain lifespan in spleen and to a lesser extent in muscle. These changes mainly involved hnRNP splicing inhibitor transcripts with most changes more marked in spleens of young animals from long‐lived strains. Changes in spleen isoform expression were suggestive of reduced cellular senescence and retained cellular proliferative capacity in long‐lived strains. Changes in muscle isoform expression were consistent with reduced pro‐inflammatory signalling in longer‐lived strains. Two splicing regulators, HNRNPA1 and HNRNPA2B1, were also associated with parental longevity in humans, in the InCHIANTI aging study. Splicing factors may represent a driver, mediator or early marker of lifespan in mouse, as expression differences were present in the young animals of long‐lived strains. Changes to alternative splicing patterns of key senescence genes in spleen and key remodelling genes in muscle suggest that correct regulation of alternative splicing may enhance lifespan in mice. Expression of some splicing factors in humans was also associated with parental longevity, suggesting that splicing regulation may also influence lifespan in humans.